(untitled) (KENOSIS: Jurnal Kajian Teologi, 2024)
Marriage as a phenomenon that has long existed in human history, in its development is now regulated in various areas, including religion. The Synod of Gereja Masehi Injili di Timor (GMIT) in its organization also formed regulations on holy marriage. Cross-Textual Hermeneutics is used to analyze the law of marriage in Deuteronomy 22:13-30 with the regulations regarding holy marriage in the GMIT’s Theological Texts and Pastoral Regulations of Holy Marriage Service. These two different texts have the same subject matter about the sanctity of marriage, adultery, rape, and divorce. However, they differ in terms of law and sanctions. The juxtaposition of these two different texts makes us aware that the dynamics of today require contextualization, including in the rules in the religious realm. Keywords: law, regulation, marriage, Deuteronomy, GMIT